Implants in disabled patients: A review and update - Romero-Pérez, María J. (Medicina Oral S.L., 2014)
The range of indications for dental implants has broadened enormously owing to their predictability and the improvement of patient satisfaction in terms of stability, comfort, aesthetics and functionality. The aim of this article is to review those indications in patients with mental or physical disabilities as the difficulty to cope with oral hygiene often leads to teeth extraction, adding edentulousness to the impairments already present. Following that goal, available literature in Pubmed database, Scopus, Web of Knowledge and The Cochrane Library database about dental implants placement in these patients has been reviewed, assessing the variables of each study: number of patients, sex, average age, oral hygiene, parafunctional habits, impairment, bone quality, protocol of implant surgery, necessity of deep intravenous sedation or general anesthesia, follow-up period and number of failures. The comparison with studies involving other patient populations without mental or physical impediments did not show statistically significant differences in terms of the failure rate recorded. Although there is not much literature available, the results of this review seem to suggest that osseointegrated oral implants could be a therapeutic option in patients who suffer from any physical or psychological impairment. The success of an oral rehabilitation depends mainly on an adequate selection of the patients. Key words:Implants, disabled, sedation.